Pengaruh E-Rating dan Kepercayaan Terhadap Keputusan Pembelian (Studi Pada Pembeli Produk Eticha di Akun Shopee Eticha_Mojokerto) - shinta chamelia; Any Urwatul Wusko (ATRABIS Jurnal Administrasi Bisnis (e-Journal), 2023)
Abstract : This research was conducted to determine "The Influence of E-Rating, and Trust in Purchasing Decisions (Study on Eticha Product Buyers on Eticha_Mojokerto Shopee Accounts)" The strategy used in this study was associative research with a quantitative approach, by distributing questionnaires as a data collection technique. The sampling method used is purposive sampling, which is a sampling technique in which people are selected as samples according to the purpose of conducting research, the sample used is 100 respondents through questionnaires. The data analysis method used in this study is Multiple Linear Analysis. The results of the study state that: (1) The E-Rating variable has no significant effect on purchasing decisions at the shopee marketplace. (2) The Trust variable has a significant effect on purchasing decisions on the marketplace shopee. (3) E-Rating and Trust variables simultaneously influence purchasing decisions on the shopee marketplace.